2019
DOI: 10.9734/air/2019/v20i430164
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Steel Square HSS Columns Strengthened with Polymer-mortar

Abstract: This paper presents the results of finite element (FE) analysis of axially loaded square hollow structural steel (HSS) columns, strengthened with polymer-mortar materials. Three-dimensional nonlinear FE model of HSS slender columns were developed using thin-shell element, considering geometric and material nonlinearity. The polymer-mortar strengthening layer was incorporated using additional layers of the shell element. The FE model has been performed and then verified against experimental results obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The binding constant ( K b ) for all the molecules in the ground state was evaluated according to the equation described previously. [ 76 ] From the plot of A o /(A‐A o ) against 1/[CT‐DNA], the binding constants, K b , can be calculated, Figure S7. It was found that the K b values are 3.84, 0.68, 1.11, 2.71, and 1.39 × 10 6 M −1 , for the free ligand Mn (II), Ni (II), Cu (II), and Co (II) complexes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding constant ( K b ) for all the molecules in the ground state was evaluated according to the equation described previously. [ 76 ] From the plot of A o /(A‐A o ) against 1/[CT‐DNA], the binding constants, K b , can be calculated, Figure S7. It was found that the K b values are 3.84, 0.68, 1.11, 2.71, and 1.39 × 10 6 M −1 , for the free ligand Mn (II), Ni (II), Cu (II), and Co (II) complexes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…EB is a sensitive fluorescent probe that emits enhanced emissive properties in the presence of DNA, as is well known. [ 76 ] In order to improve and support the type of complex binding with CT‐DNA, the absorption and emission measurements of EB bound DNA were tested using Mn (II), Co (II), Ni (II), and Cu (II) complexes. The absorption and emission spectra of EB bound CT‐DNA in the absence and presence of various concentrations of the metal complexes were shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…[ 96 ] The binding constants for HL, C 1 , C 2 , C 3 and C 4 are good as compared with classical intercalators confirming a moderate intercalative interaction. [ 97–99 ]…”
Section: Resultsmentioning
confidence: 99%
“…The optical bandgap energy (Enormalgopt) of the thin films is determined from Tauc plots based on the relation ( αhν ) n = α 0 ( hν − Enormalgopt), where α , h , ν , n , and α 0 are the absorption coefficient, the Planck's constant, the frequency of the photon, the exponent that characterizes the optical absorption process, and an adjustable constant, respectively. [ 10,21,22 ] In case of a‐Ga 2 Te 3 , n = 1/2 is applied because of its nature of an indirect bandgap semiconductor. [ 23–26 ] The Enormalgopt can be estimated from the x intercept on the plots of ( ahν ) 1/2 versus hν, as shown in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%